Common Tomato High Tunnel Production Diseases in Florida - Zachary D. Eldred; Shufang Tian; Gary E. Vallad; Xin Zhao; Mathews Paret; Nicholas S. Dufault (EDIS)
This new 7-page article provides a concise overview of some influential high-tunnel tomato soilborne and foliar diseases and their cultural management techniques. Written by Zachary D. Eldred, Shufang Tian, Gary E. Vallad, Xin Zhao, Mathews Paret, and Nicholas S. Dufault and published by the UF/IFAS Plant Pathology Department. https://edis.ifas.ufl.edu/pp368